1979
DOI: 10.2190/cucp-50lf-yyrx-70wr
|View full text |Cite
|
Sign up to set email alerts
|

The Index as Editor

Abstract: No one doubts that indexes are of value to readers. But they can also be of value to their own authors as editing tools. Because an index provides a microcosm of the main text, errors in that text will often be reflected in the index, and reflected in a way that makes them more visible. As he creates the index, the author can use it to spot errors in the body of the work—errors of terminology, of arrangement, of proportion, and of omission. This technique can be used to supplement the normal editing process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
1987
1987

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In a sense, this division between the processes of generation and revision is too rigid. The use of tools such as automatic indexing systems (e.g., Bethke, 1979) can both facilitate the generation of material and also provide the author with insights concerning the structure and coverage of the text. These insights, in their turn, may facilitate revision.…”
Section: B Computer-assisted Writingmentioning
confidence: 99%
“…In a sense, this division between the processes of generation and revision is too rigid. The use of tools such as automatic indexing systems (e.g., Bethke, 1979) can both facilitate the generation of material and also provide the author with insights concerning the structure and coverage of the text. These insights, in their turn, may facilitate revision.…”
Section: B Computer-assisted Writingmentioning
confidence: 99%
“…Software may also offer valuable support when it comes to chores such as compiling indexes. Bethke (1979) has suggested that the creation of an index can itself be a design tool, since it can highlight errors of terminology and organisation within a manual.…”
Section: Gillilandmentioning
confidence: 99%